The impact of weight self‐stigma on weight‐loss treatment engagement and outcome - Samantha J. Schram; KayLoni L. Olson; Emily Panza; Jason Lillis (Obesity Science & Practice)
Abstract Background Individuals with overweight or obesity often endure significant weight‐based prejudice and discrimination in various settings. Experiencing weight‐related stigma is linked to many adverse psychosocial outcomes. Weight self‐stigma is when an individual internalizes and identifies with negative attributes ascribed to people with larger bodies and has self‐devaluing thoughts because of their weight and is associated with poorer health outcomes. Aims This study explored how weight self‐stigma may impact weight management efforts and outcomes for adults participating in an onlight weight‐loss intervention. Materials and Methods 508 adults (86.2% female, 84.6% White) with overweight or obesity participated in an asynchronous 12‐week online weight‐loss intervention with computer‐generated feedback. Weight and weight self‐stigma were measured at baseline and 3 months later. Results Thirty‐one point five percent of the sample reported high levels of stigma, which was associated with greater program dropout than those who did not report high stigma (32.5% vs. 21.6%). Program completers reporting high self‐stigma showed better treatment engagement (77.0% vs. 69.7% lessons viewed) and weight loss (M = −6.31% vs. −5.08%); these differences were not observed when using intent‐to‐treat assumptions. When analyzed as a continuous variable, weight self‐stigma showed no association with treatment engagement and outcome. Discussion These findings highlight the complexity of understanding how self‐stigma affects treatment engagement and outcome in behavioral weight loss and the need for more targeted research in this understudied area. Conclusion Results suggest that weight self‐stigma plays a role in weight management during an online weight‐loss intervention, affecting engagement and outcomes.